Prediction of the progression of walled‐off necrosis in patients with acute pancreatitis on whole pancreatic perfusion CT. (6th August 2020) - Yamamiya, Akira; Kitamura, Katsuya; Yoshida, Hitoshi; Ishii, Yu; Mitsui, Yuta; Irisawa, Atsushi
Abstract: Background/Purpose: This study investigated whether measuring pancreatic blood volume (PBV) on whole pancreatic perfusion computed tomography (P‐CT) can predict the progression of walled‐off necrosis (WON) in patients with acute pancreatitis (AP). Methods: A single‐center, retrospective cohort study was conducted between December 2015 and December 2016. The participants were divided into two groups: 14 patients with WON and 15 patients without WON. PBV was measured within 72 hours after the diagnosis of AP, and the final diagnosis of WON was made by contrast‐enhanced CT (CE‐CT) or endoscopic ultrasonography (EUS) 4 weeks after the onset of AP. Results: The minimum CT value did not differ significantly between the two groups. On the other hand, the minimum PBV was significantly lower in the WON group than in the without WON group (1.4 (0.9–9.9) vs 19.8 (8.2–21.7) mL/100 mL, respectively; P  = .02). The cutoff value of the minimum PBV for WON was 16.5 mL/100 mL (sensitivity 100%, specificity 67%, AUC 0.85; P  = .001). Conclusions: Whole pancreatic P‐CT can evaluate pancreatic ischemia visually and quantitatively. The minimum PBV measurement on whole pancreatic P‐CT within 72 hours after the diagnosis of AP contributes to the prediction of progression of WON. Abstract : Highlight In this retrospective study, Yamamiya and colleagues demonstrated that whole pancreatic perfusion computed tomography allowed both visual and quantitative evaluation of pancreatic ischemia, and concluded that the minimum pancreatic blood volume measurement within 72 hours after the diagnosis of acute pancreatitis was useful for predicting the progression of walled‐off necrosis.